Numerical and physical modeling of submarine telecommunication cables subjected to abrupt lateral seabed movements. Issue 11 (4th November 2021) - Wang, Yu; Fu, Cuiwei; Qin, Xiaogang
Abstract: Submarine telecommunication cables, which carry about 99% of international telecommunications, are usually buried shallowly beneath seabed and vulnerable to seabed movements. In recent years, many submarine cable damages have been observed when significant lateral seabed movements occur due to geohazards, e.g., offsets of strike-slip faults and submarine landslides. However, research on the interaction between submarine telecommunication cables and lateral seabed movements is limited. There is no existing method for evaluating the cable safety when subjected to lateral seabed movements. This paper aims to carry out finite element (FE) analysis and physical modeling to investigate the responses of submarine telecommunication cables to lateral seabed movements. A FE model is developed and validated by full-scale physical test results. After validation of the FE model, a series of parametric studies is performed covering typical ranges of soil properties, cable burial depths, cable characteristics and seabed movement characteristics. The parametric study results are summarized in a dimensionless plot, followed by a regression analysis. A simple but effective formula is proposed to predict the maximum cable strains induced by lateral seabed movements. The dominant parameters that control submarine cable responses are identified and incorporated into the formula. Safety criteria for submarine telecommunication cables are also proposed for evaluating the cable safety when subjected to lateral seabed movements.